PENGEMBANGAN MEDIA PEMBELAJARAN IPA BERBASIS POWTOON PADA POKOK BAHASAN KLASIFIKASI MATERI DAN PERUBAHANNYA DI TINGKAT SMP - Annisaa Dwi Ayu Permatasari; Dinar Maftukh Fajar (Program Studi Pendidikan IPA FKIP Universitas Jember, 2022)
The development of Powtoon-based learning media on the subject of Classification of Materials and Its Changes at the junior high school level was carried out based on the problems that researchers found at SMP Negeri 1 Gending, Probolinggo, East Java, namely the decrease in students' enthusiasm for learning during COVID-19 outbreak, the lack of learning media that can be utilized, and the amount of material that must be mastered. This paper aims to describe the validity and students' responsesto the Powtoon based learning media on the subject of Classification of Materials and Its Changes at the junior high school level. The type of research carried out is research and development with a 4-D model (define, design, development and dissemination) where the dissemination stage is not implemented. The products that were successfully developed were 3 learning videos uploaded and distributed through Youtube.com. The results of the assessments of media experts, material experts, and product user teachers are included in the very valid category. The recapitulation of student responses gave positive results. Descriptions of student responses are mapped in the form of a Word Cloud with the words “interesting”, “excited”, “learning”, “understand” are words often mentioned. Students argue that this media has advantages from the animation aspect so that it grows attractiveness and motivation in learning.